LAPAROSCOPIC REDO FUNDOPLICATION ALONE, REDO NISSEN FUNDOPLICATION, OR TOUPET FUNDOPLICATION COMBINED WITH ROUX-EN-Y DISTAL GASTRECTOMY FOR TREATMENT OF FAILED NISSEN FUNDOPLICATION - Italo Braghetto; Owen Korn; Manuel Figueroa-Giralt; Catalina Valenzuela; Ana Maria Burgos; Carlos Mandiola; Camila Sotomayor; Eduardo Villa (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2022)
ABSTRACT BACKGROUND: Laparoscopic Nissen fundoplication fails to control the gastroesophageal reflux in almost 15% of patients, and most of them must be reoperated due to postoperative symptoms. Different surgical options have been suggested. AIMS: This study aimed to present the postoperative outcomes of patients submitted to three different procedures: redo laparoscopic Nissen fundoplication alone (Group A), redo laparoscopic Nissen fundoplication combined with distal gastrectomy (Group B), or conversion to laparoscopic Toupet combined with distal gastrectomy with Roux-en-Y gastrojejunostomy (Group C). METHODS: This is a prospective study involving 77 patients who were submitted initially to laparoscopic Nissen fundoplication and presented recurrence of gastroesophageal reflux after the operation. They were evaluated before and after the reoperation with clinical questionnaire and objective functional studies. After reestablishing the anatomy of the esophagogastric junction, a surgery was performed. None of the patients were lost during follow-up. RESULTS: Persistent symptoms were observed more frequently in Group A or B patients, including wrap stricture, intrathoracic wrap, or twisted fundoplication. In Group C, recurrent symptoms associated with this anatomic alteration were infrequently observed. Incompetent lower esophageal sphincter was confirmed in 57.7% of patients included in Group A, compared to 17.2% after Nissen and distal gastrectomy and 26% after Toupet procedure plus distal gastrectomy. In Group C, despite the high percentage of patients with incompetent lower esophageal sphincter, 8.7% had abnormal acid reflux after surgery. CONCLUSIONS: Nissen and Toupet procedures combined with Roux-en-Y distal gastrectomy are safe and effective for the management of failed Nissen fundoplication. However, Toupet technique is preferable for patients suffering from mainly dysphagia and pain.